Manual Vacuum Aspiration vs Vaginal Misoprostol for the Management of First-Trimester Incomplete Miscarriage in term of complete abortion - Shams un Nisa, Sadaf un Nisa, Mahnoor Athar, Nadia Zulfiqar, Bilqees Akhtar Malik, Mahjabeen Hira, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the complete abortion rate between manual vacuum aspiration and vaginal misoprostol for the management of First-Trimester Incomplete Miscarriage in term of complete abortion Study design: Randomized Controlled Trial. Study duration: April 2022 to October 2022. Setting: Department of Obstetrics & Gynecology Bahawal Victoria Hospital Bahawalpur. Methods: A total of 120 patients with First-Trimester Incomplete Miscarriage were chosen and equally divided into the MVA group and the MM group. The effectiveness of achieving a complete abortion was compared between the two groups. Results: Total 120 patients were selected. In MVA group, mean age and mean gestational was 31.47±5.82 years and 6.92±3.39 weeks while in MM group was 30.87±6.86 years and 5.78±3.47 weeks. Complete abortion was noted in 53(88.33%) patients of MVA group while in 44(73.33%) patients of MM group. Significantly (P=0.036) higher Efficacy (Complete abortion) rate was noted in MVA group. Practical Implication: It is a very good option in hospitals with low resources and in developing countries like Pakistan. Conclusion: In this study, we found MVA had higher complete abortion rate as compared to misoprostol intra vaginally. So, MVA is better treatment option than misoprostol intra vaginally as it has no systemic effects and it is a very good option in hospitals with low resources and in developing countries like Pakistan. Key words: Miscarriage, MVA, vaginal misoprostol, incomplete abortion, Gynecology, Pakistan